New Trends in E-service and Smart Computing - Matsuo, Tokuro; Mine, Tsunenori; Hirokawa, Sachio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book examines theoretical and practical aspects of emerging technologies in e-service and artificial intelligence from an academic and professional viewpoint. To do so, it focuses on three major areas: the development of novel user support systems; development of smart mobility; and emerging technologies in Artificial Intelligence (AI). With regard to the development of novel user support systems, Chapter 1 introduces alternative ingredients recommendation using data on co-occurrence relation and ingredients categories to support cooking, while Chapter 2 introduces a study on location information inference using data acquired by low-energy Bluetooth devices. Turning to the development of smart mobility, Chapter 3 highlights a sustainable information infrastructure project for smart mobility systems. In addition, Chapter 4 presents a lifecycle-oriented development process to improve requirements and design in terms of uncertainties to provide sustainable information architectures for smart mobility. In the book's third and last part - emerging technologies in AI - Chapter 5 presents a summarization task for sports events on Twitter, focusing on an abstractive approach based on sub-events during the sports event. Chapter 6 discusses the generation of headlines using a recurrent neural network based on a machine translation approach. Lastly, Chapter 7 explores customer behavior analysis using enthusiasm analysis, an approach that estimates customers' activation levels. The book gathers a selection of the highest-quality papers presented at the 4th International Congress on Advanced Applied Informatics, held on July 12-16, 2015 in Okayama, Japan. Given the breadth of its coverage, it offers a valuable resource for practitioners, researchers and students alike.
Co-occurrence Relation" and "Ingredient Category" Recommend Alternative-ingredients -- Design and Initial Evaluation of Bluetooth Low Energy Separate Channel Fingerprinting -- Toward Sustainable Smart Mobility Information Infrastructure Platform ：-Project Overview- -- Model-based methodology Establishing Traceability between Requirements, Design and Operation Information in Lifecycle-Oriented Architecture -- Sports game summarization based on sub-events and game-changing phrases -- Headline Generation with Recurrent Neural Network -- Customer State Analysis with Enthusiasm Analysis.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence